Association of genome variations in the renin-angiotensin system with physical performance - Sgourou Argyro; Fotopoulos Vassilis; Kontos Vassilis; Patrinos George P; Papachatzopoulou Adamantia (Human Genomics, 2012)
Abstract Background The aim of this study was to determine the genotype distribution and allelic frequencies of ACE (I/D), AGTR1 (A +1166 C), BDKRB2 (+9/−9) and LEP (G–2548A) genomic variations in 175 Greek athletes who excelled at a national and/or international level and 169 healthy Greek adults to identify whether some particular combinations of these loci might serve as predictive markers for superior physical condition. Results The D/D genotype of the ACE gene (p = 0.034) combined with the simultaneous existence of BDKRB2 (+9/−9) (p = 0.001) or LEP (G/A) (p = 0.021) genotypes was the most prevalent among female athletes compared to female controls. A statistical trend was also observed in BDKRB2 (+9/−9) and LEP (G–2548A) heterozygous genotypes among male and female Greek athletes, and in ACE (I/D) only in male athletes. Finally, both male and female athletes showed the highest rates in the AGTR1 (A/A) genotype. Conclusions Our results suggest that the co-existence of ACE (D/D), BDKRB2 (+9/−9) or LEP (G/A) genotypes in female athletes might be correlated with a superior level of physical performance.